O incentivo fiscal para área social: uma reflexão sobre as leis de incentivo e o caso do esporte nos países latinos da América do Sul - Rafael Silva Diniz (2023)
The Sport Incentive Law is configured as a public policy that creates a special rule within the Brazilian tax system aimed at inducing the taxpayer's behavior to be more supportive of the cause of sport and leisure. For this, in the Income Tax Declaration, there is authorization for the taxpayer to deduct the financial contributions made to the sport. However, the legislation allowed the support amounts to be fully deducted, causing the private resource to be absorbed as public investment. In other words, the mechanism made the business sector gain fame, by stamping its brand on the projects, but the sports sponsor is the Brazilian State itself, which fully assumes the burden of investment. Would this be a “Brazilian way” to encourage private action in social causes, based on an expectation of raising awareness in the business sector, or a model of public policy that also exists in other countries? Upon this questioning, the present work sought to expand knowledge about tax incentive laws for the social area, initially exploring the history of the case of culture and then of sport, and then the operation in Peru, Uruguay and Chile, the three Latin countries in South America that also have sports patronage. By analyzing the history of bills and parliamentary debate on the Sports Incentive Law, we identified that the lack of financial compensation came from the government's fear of proposing a discount percentage, since public policy had already been denied in other occasions. In addition to Brazil, Peru also has a similar patronage mechanism, but focused only on high-performance sports. However, Peruvian patronage is a promotion program within a broader policy for the development of national sport. The same is the case of sports patronage in Uruguay, which despite having a financial counterpart, complements the public investment policy in promoting high-performance sports. In Chile, the sports patronage policy covers several sports events, as in Brazil, but makes use of a public investment fund to balance the distortions caused in the private allocation of the resource. This public fund is also promoted by private resources coming from Chilean patronage. During this work, it was also possible to verify that the discourse of low investment in sport is always a material situation for requesting the state patronage policy, but other external factors are necessary for its creation. In the case of Brazil, Peru and Uruguay, the holding of Sports Mega-Events was a pressure factor for the approval of sports sponsorship legislation. Meanwhile, in Chile, a scenario of a high level of sedentary lifestyle among the population helped to elevate physical activity and sport to a public health issue, allowing the inclusion of tax exemption in the General Standard for Sport